Evil Eye in Sunni and Shi'ite Exegeses - Reza Baqizadeh Palami (پژوهش‌های تفسیر تطبیقی, 2019)
One of the questions propounded in the society is whether the evil eye is factual or imaginary. This study aims to review the evil eye form Sunni and Shi'ite perspectives. Since many people are concerned with this issue, it seems essential to discuss and analyze this subject. This research has been accomplished by descriptive analysis and data collection through library method and note taking. The results of the study show that according to what has been stated in Sunni and Shi'ite exegetical books, the evil eye is not only superstition but also it is confirmed by some verses in the Qur'an and various narrations. It means that some people have a sort of power which is supernaturally effective; and the extent of which depends on those people. Moreover, some guidelines have been suggested to ward off and dispel this negative energy. Received: 10/8/2018   |   Accepted: 2/11/2018